2016
DOI: 10.1159/000443413
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell-Derived Extracellular Vesicles Protect Against Acute Kidney Injury Through Anti-Oxidation by Enhancing Nrf2/ARE Activation in Rats

Abstract: Background/Aims: Anti-oxidation is an effective strategy for curing acute kidney injury (AKI). Herein, we suggest that extracellular vesicles (EVs) derived from mesenchymal stromal cells (MSCs) might play an anti-oxidative role by enhancing Nrf2/ARE activation in AKI. Methods: EVs isolated from the conditioned medium of human Wharton's Jelly mesenchymal stromal cells and human foreskin fibroblast were intravenously injected in rats immediately after 45 min of unilateral kidney ischemia. Animals were sacrificed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 34 publications
2
107
0
2
Order By: Relevance
“…This work confirms previous findings that EVs from kidney-derived MSC are involved in the recovery from AKI following IRI by promoting the proliferation of peri-tubular capillary ECs and decreasing peritubular microvascular rarefaction, possibly by acting as carriers of pro-angiogenic signals (Choi et al, 2014). In addition, several works demonstrated that the therapeutic effect of EVs derived from MSC (MSC-EVs) (Herrera et al, 2007; Bruno et al, 2012; Zhang et al, 2016) was mainly due to the transfer of their miRNA content (Collino et al, 2015) in AKI and other renal injuries. Moreover, EVs derived from other stem cells, such as human liver stem cells (HLSCs), showed to be effective in AKI recovery in vivo (Herrera Sanchez et al, 2014).…”
Section: Therapeutic Application Of Evs In Renal Pathologymentioning
confidence: 99%
“…This work confirms previous findings that EVs from kidney-derived MSC are involved in the recovery from AKI following IRI by promoting the proliferation of peri-tubular capillary ECs and decreasing peritubular microvascular rarefaction, possibly by acting as carriers of pro-angiogenic signals (Choi et al, 2014). In addition, several works demonstrated that the therapeutic effect of EVs derived from MSC (MSC-EVs) (Herrera et al, 2007; Bruno et al, 2012; Zhang et al, 2016) was mainly due to the transfer of their miRNA content (Collino et al, 2015) in AKI and other renal injuries. Moreover, EVs derived from other stem cells, such as human liver stem cells (HLSCs), showed to be effective in AKI recovery in vivo (Herrera Sanchez et al, 2014).…”
Section: Therapeutic Application Of Evs In Renal Pathologymentioning
confidence: 99%
“…Oxidative stress or electrophilic stress disrupts critical cysteine residues in Keap-1, translocating Nrf2 into the nucleus, where Nrf2 binds to the antioxidant response element (ARE) in the upstream promoter region of many antioxidative genes and initiates their transcription [10]. Activation of Nrf2 could induce many cytoprotective proteins such as heme oxygenase-1 (HO-1), an enzyme that catalyzes the degradation of heme into the antioxidant biliverdin, the anti-inflammatory agent carbon monoxide, and ferrous iron [11-13]. HO-1 is a highly inducible isoform in response to stress such as oxidative stress, I/R, hypoxia, heavy metals, cytokines, and nitric oxide [14-16].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is another important factor in renal injury repair, especially in ischemic reperfusion-induced acute kidney injury [18]. The regulation of oxidative stress by MSCs and EVs has been widely reported in renal injury repair [19, 20]. Here, we found that EVs show showed more potency in oxidative stress pathways related to the DUSSP8 and MKNK2 genes than MSCs, as indicated by miRNA levels.…”
Section: Discussionmentioning
confidence: 53%